(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Tourism is slowly waking up after COVID-19, and travel leaders are looking for ways to save their businesses. Participants in the tourism market have been interested in AR and VR for some time. But how will these tools affect the industry post-pandemic? As the demand for travel and hospitality services increases, we are seeing a growing interest in AR and VR tourism. Travel and tourism companies are investing in AR and VR development to increase bookings and provide more engaging experiences to their customers. Apps are being developed to help customers access real-time versions of the destinations they want to visit.